A retrospective view of informalilty in Bogota - Mendoza, Pilar (2015)
Heavy civil riots occurred in Bogota on April 9th, 1948, the day when the popularleader Jorge Eliecer Gaitan was killed. This popular insurrection had deep consequences which reflect to the present-day construction of the city. Crowds of people from the popular districts of the city took part in demonstrations that resulted in the death of about 3,000 people and destroyed parts of the historic center and some symbolic places. Subsequently, the rebellion spread throughout the whole country. After this historic event, which is known as the ‘Bogotazo’, the modernization, which had started beforehand, sped up in a radical way. At the same time, the ingression of new inhabi- tants from the surrounding region increased significantly, resulting in Bogota developing into the metropolis it is today. The poor and working class population started with the invasion and the construction of ‘pirate quarters’ in the southern suburban area and in the eastern hills, while the rich population started moving toward the north of the city. In this way, the suburbs seem to be a projection of the city but in a rather unplanned way, which have mainly been generated by the population itself. In this way we describe the process in which working class people took possession of a large city, and the way in which a city was informally developed, resulting in the creation of suburban quarters.